Effects of L-fucose supplementation on the viability of cancer cell lines - Mazlan, Muhammad Alif; Yusof, Afzan Mat; Md Isa, Muhammad Lokman (UI Scholars Hub, 2020)
Background: Fucose is a deoxyhexose sugar. While the biological roles of L-fucose remain unclear, the sugar is known to accelerate the malignant potential of cancer cells. Therefore, this study aimed to evaluate the viability pattern of human cancer and normal cell lines treated with fucose. Methods: The human gingival fibroblast (HGF-1), colorectal adenocarcinoma (HT-29) and skin malignant melanoma (A375) cell lines were cultured and treated with fucose at three concentrations of 1, 5, and 10 mg/ml. Cell viability was then measured using (3-(4, 5-dimethylthiazolyl-2)-2, 5-diphenyltetrazolium bromide (MTT) assay. The data were analyzed using Statistical Package for the Social Sciences software. Results: The percentage of HGF-1 cell viability showed a rapid decline after day 1 of treatment. HT-29 and A375 were capable of surviving treatment with high fucose concentrations. The data were highly significant at p < 0.001. Conclusion: Whereas a high concentration of fucose is toxic to the HGF-1 cell line, the HT-29 and A375 cell lines could potentially adapt to this condition. Down- or upregulation of certain molecules that could induce or inhibit cell death may explain such adaptation. Further testing of up- and downregulated molecules should be conducted in future work.